Correlation between SERS of Pyridine and Electrochemical Response of Silver Electrodes in Halide-Free Alkaline Solutions - Temperini, M. L. A. (1988)
Surface-enhanced Raman scattering (SERS) of pyridine (Py) on Ag electrodes in alkaline solutions free of halide ions was obtained at 25°C as a function of the applied potential. The Ag surface was activated for SERS through repetitive oxidation-reduction cycles (ORC), the effect being dependent on the electrochemical electrode history. The SERS effect was correlated to the activation for the hydrogen evolution reaction (HER), which can be obtained by means of potentiodynamic as well as potentiostatic procedures. The maximum SERS activity was achieved at potentials near the potential of zero charge (pzc) of polycrystalline Ag and appeared to be related to the maximum observed in the roughness factor vs potential curve. These results can be interpreted through the formation of a new uniform globular overlayer structure on the electroreduced Ag surface, which apparently exhibits a certain degree of preferred crystallographic orientation. Three well-defined potential regions can be distinguished for the complex competitive interactions between H2O, OH- ion, and Py with the new Ag electrode surface.